Subthreshold Micropulse Treatment Laser versus Half-Dose Photo Dynamic Therapy for the Chronic Central Serous Chorioretinopathy with Parafoveal or Subfoveal Leakage STML versus PDT for Treatment of Chronic CSC - Qingshan Chen; Xia Zhao; Qiuju Yin; Zhi Li; Zimei Zhao; Jiafeng Ning (Journal of Ophthalmology)
Purpose. The study aimed to compare the efficacy and safety outcomes of a subthreshold micropulse treatment laser (SMTL) versus half-dose photodynamic therapy (PDT) for treatment of chronic central serous chorioretinopathy (cCSC) with parafoveal or subfoveal leakage to persistent subretinal fluid. Methods. One hundred and forty-eight patients (148 eyes) with persistent cCSC were enrolled in this retrospective study and treated with SMTL or half-dose PDT. All patients were diagnosed according to clinical characteristics and findings on multimodal imaging. The medical records including patients with a minimum follow-up period of 3 months were reviewed. The patients were divided into two groups according to the application of the SMTL or PDT. The group of the SMTL or PDT was also divided into two subgroups according to parafoveal or subfoveal leakage. The primary outcomes included best-corrected visual acuity (BCVA) and central retinal thickness (CRT) before and 1, 2, and 3 months after treatment. The repeat treatment and resolution of subretinal fluid were also collected. Results. Seventy-nine patients (79 eyes) treated with half-dose PDT and 69 Patients (69 eyes) treated with the STML were included. The mean age was 44.20 ± 7.42 years and 80% were male. No significant difference in age, gender, baseline logMAR BCVA or CRT between the half-dose PDT group and the SMTL group (P=0.201; 0.051) can be defined. The BCVA of the SMTL group improved at 1, 2, and 3 months after treatment, while that of the half-dose PDT group improved like the SMTL group. There were no significant differences between the SMTL and the PDT group at 1, 2, and 3 months (P=0.723; 0.139; 0.896). The CRT for the SMTL group decreased at 1, 2, and 3 months after treatment, while that of the half-dose PDT group changed like the SMTL group. However, there were significant differences between the SMTL group and the PDT group at 1and 3 months (P=0.010; 0.009). 13/69 (18.84%) and 9/79 (11.39%) patients underwent treatment at least twice in the SMTL and half-dose PDT group, respectively, and achieved resolution of SRF after treatment. The results of subgroups analysis showed no significant differences between the logMAR BCVA of the SMTL and PDT group which were divided into parafoveal and subfoveal leakage groups after treatment, but significant difference in CRT between subgroups can be found after treatment at 1and 3 months (P=0.003; 0.04). Conclusions. The SMTL can be an effective candidate for the treatment of persistent cCSC where leakage occurred at parafoveal or subfoveal and improvement of logMAR BCVA, but half-dose PDT has been more effective for resolution of SRF.